2017
DOI: 10.5433/1679-0359.2017v38n3p1383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and cyclical heat stress on the serum biochemical profile of broiler chickens

Abstract: This study aimed to evaluate the influence of age and cyclical heat stress for 1 hour per day on the levels of serum proteins, metabolites, and enzymes in broiler chickens of 21-42 days of age. We used 420 male broiler chickens, Cobb Avian48TM breed, in a completely randomized experimental design, composed of two treatments and six replicates. The treatments consisted of two thermal environments: one in which broiler chickens were raised under natural conditions of temperature and humidity for the first 42 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
(19 reference statements)
6
20
0
2
Order By: Relevance
“…This was not observed in the present study, possibly because the broilers recovered from the effects of stress during the warmest part of the day. This adaptation response of broilers to cyclic heat stress was also discussed by Bueno et al (2017) and Balnave (2004), who observed a compensatory gain (in performance or in physiology) of broilers during periods when temperature draws near to thermal comfort, most often at nighttime.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This was not observed in the present study, possibly because the broilers recovered from the effects of stress during the warmest part of the day. This adaptation response of broilers to cyclic heat stress was also discussed by Bueno et al (2017) and Balnave (2004), who observed a compensatory gain (in performance or in physiology) of broilers during periods when temperature draws near to thermal comfort, most often at nighttime.…”
Section: Discussionsupporting
confidence: 59%
“…found that albumin is the main carrier protein of thyroidal hormones. Based on the albumin levels found by Bueno et al (2017) in a study that used broilers exposed to cyclic heat stress, the highest levels of albumin are observed in broilers on days 28 and 42 of age. This means that it is possible that T was efficiently converted into T 3 on day 28, when metabolism is high, since the concentration of T 4 was the lowest and T 3 levels were still high.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress and the lines did not influence small intestine morphometry (Table 3). In the present study, heat stress was cyclic (one to three daily hours under high temperatures and 23 to 21 h under ideal temperatures); thus, the finding that small intestine morphometry was not changed by heat can be partly explained by the compensation occurring at nighttime and in the other moments when the birds were under ideal temperatures (BALNAVE, 2004;BUENO et al, 2017). As regards the line, a possible explanation for the lack of effects is that body weight did not differ between the two (Table 4).…”
Section: Resultsmentioning
confidence: 59%
“…A presumed interpretation for the lack of differences in density and mineral matter of the tibia between the thermal environments is the fact that mineral deposition in the bird skeleton is more intense in the initial weeks; i.e., until 21 days of age (OLIVEIRA et al, 2014); thus, the seven days of exposure to high temperatures (14 to 21 days of age) were not sufficient to cause alterations in mineral matter and density, in relation to the 14 days the birds remained under comfort. Moreover, the intensity and duration of heat stress were not sufficient to affect mineral deposition in the tibia, since the birds managed to recover from the stress they had undergone during the fresher times of the day (BALNAVE, 2004;BUENO et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol level in heat treated birds was higher than that of control on the 3 rd day (+8.38%), but on the 10 th day, it was +20% (P<0.05). Sohail et al (2010), Xie et al (2015) and Rodrigues Bueno et al (2017) also reported similar cholesterol level in broilers under heat stress. Serum calcium and phosphorus of the treatment group were showing significantly lower values (P<0.05).…”
Section: Serum Biochemical Parametersmentioning
confidence: 52%